Maximizing Artificial Intelligence for Patient Satisfaction: Marketing Strategies in The Digital Health Era - Anggi Parsaoran Hotmangatur; Adang Bachtiar (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The advent of the Fourth Industrial Revolution has catalyzed transformative changes in the healthcare sector, highlighting the need to optimize Artificial Intelligence (AI) to improve patient satisfaction. This research examines the role of AI in revolutionizing the healthcare market and its potential to improve patient outcomes. Using a systematic literature review, we collected and analyzed studies published from 2017 to 2022 from various databases such as ProQuest, Science Direct, PubMed, CINAHL, and Scopus, focusing on AI applications in healthcare and its impact on patient satisfaction. Inclusion criteria for the initial screening were articles that were freely available in full text, had open access, and were published in English or Indonesian, as well as ensuring no duplication in the records found. Significant findings were synthesized through thematic and descriptive analysis to ascertain the efficacy of AI in patient care. Of the 25 articles relevant for further evaluation, 12 studies met the inclusion criteria and were included in the qualitative analysis. The chosen methodology allowed the authors to conduct a comprehensive and systematic review. A practical suggestion that can be drawn from these findings is the importance of investing in the development of artificial intelligence (AI) in healthcare. This requires adequate training for staff to understand and use these technologies effectively. In addition, healthcare institutions should ensure that the use of AI remains compliant with applicable privacy and ethical regulations. Collaboration between various parties such as healthcare institutions, technology providers, and researchers is also necessary to accelerate innovation and knowledge exchange. By utilizing real-time data analysis powered by AI, healthcare can be improved, and governments can support innovation in AI by providing incentives, supportive regulations, and adequate research funding. Keywords: Artificial Intelligence, Digital Transformation, Healthcare Revolution, Patient Satisfaction, Service Optimization